MEASUREMENT OF THE EFFICIENCY OF SME CLUSTER USING DATE ENVELOPMENT ANALYSIS (DEA) - Ma'ruf Ma'ruf; Sidiq Permono Nugroho; Anton Agus Setyawan; Muzakar Isa (Muhammadiyah International Journal of Economics and Business, 2018)
This study explored the efficiency of SME Cluster. We developed an efficiency model consistingof operational capital, labor cost and raw material cost as the inputs. We proposed sales revenueand assets as the outputs of the model. Furthermore, a survey was conducted by involving 83SMEs in three different clusters. These three different clusters were batik cluster, furniture cluster,and apparel cluster. These clusters had been considered as SMEs with large labor absorption andenormous productivity, particularly in the area of Central Java, Indonesia. Our result shows thatmost SMEs included in those three clusters are not efficient in operating their businesses. Themain problem is related with the cost structure, especially in costly raw materials. In addition, itis suggested to improve the performance of human resource in those SMEs.